SPENT BLEACHING EARTH-BIOPROCESS (SBE) CHARACTERISTICS AGAINST INDONESIAN NATIONAL REGULATION FOR TOXIC-HAZARD WASTE AND SOIL AMENDMENT - Kurnia, Asep; Harsanti, E.S.; Ardiwinata, Asep Nugraha; Sutriadi, Teddy; Yusuf, Wahida Annisa; Gunawan, Bambang (JURNAL STANDARDISASI, 2024)
Currently, the palm oil industry disposes the Spent Bleaching Earth (SBE) to the land-field without a proper treatment process. Some peoples argue that the SBE still in high oil content and will pose an environmental problem due to hazardous content and it will easily catch fires. One possible solutions is optimizing SBE for land restoration, which could also be enhancing livelihood and reducing pollution. This paper identifies the SBE-bioprocess according to the Indonesian National Regulation for toxic-hazard waste and soil rehabilitation. SBE-bioprocess testing was conducted as toxic-hazard waste both on TCLP organic and anorganic form also as a soil amendment criteria both certain function and organic. Research shows that the SBE-bioprocess could not be categorized as toxic-hazard waste due to very low value of toxic and hazard compounds. Additional C-organic is important before using it as an organic soil amendments. Lab test shows that SBE-bioprocess is high value of CEC, then could be developed for specific function of soil amendments.